The Value Of Local Wisdom Of Sasi In Clove Plants In Sepa Country Amahai District Central Maluku Regency - Iin Mutia Patty; J.F. Sopamena; Jeter. D. Siwalette (International Journal of Economics, Business and Innovation Research, 2024)
This research aims to determine the value process and application of clove plant sasi in Negeri Sepa and to find out the economic, social and environmental aspects of the clove plant sasi of the Negri Sepa community. This research is a qualitative research. This research was carried out for 1 month, namely in October – November 2023. The location of this research was carried out in Negeri Sepa, Amahai District, Central Maluku Regency. The sample in this research were 15 clove farmers in Negeri Sepa. Data collection techniques use interviews, observation and documentation. Data analysis includes data reduction, data presentation, and conclusions/verification. The results of the research show that the value and application of the sasi custom to clove plants among the people of Negeri Sepa aims to preserve one of the legacies handed down from their ancestors that exists to this day, besides that, the community also believes that with this sasi tradition they can protect forest products or clove plants from thieves. With the implementation of sasi which is still maintained in Negeri Sepa, Amahai sub-district, natural resources can be directly conserved so that they do not become extinct and can be used by the next generation. The economic, social and environmental aspects of clove plantations in Negeri Sepa have different functions. The economic aspect "includes the community's efforts to meet life's needs. The social aspect includes sasi reducing the potential for theft. And the environmental aspect can be seen from the existence of well-maintained land in Cengkeh Hamlet so that the surrounding environmental ecosystem and people's lives become orderly and better.